2001
DOI: 10.1111/j.1365-2621.2001.tb15198.x
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoid Content and Physicochemical and Sensory Characteristics of Carrot Chips Deep‐Fried in Different Oils at Several Temperatures

Abstract: The influence of deep-frying using different oils and temperatures on carotenoid content and physicochemical and sensory characteristics of carrot chips was investigated. Sliced carrots were steam-blanched, cooled, soaked in 0.2% sodium metabisulfite, and deep-fried in canola, palm, or partially hydrogenated soybean oil (PHSO) at 165, 175, or 185 Њ Њ Њ Њ ЊC. Frying temperature, but not oil, significantly (P Ͻ Ͻ Ͻ Ͻ Ͻ 0.05) affected the ␣ ␣ ␣ ␣ ␣-carotene, ␤ ␤ ␤ ␤ ␤-carotene, and total carotenoid contents. Oil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
55
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 50 publications
6
55
1
Order By: Relevance
“…Cooking, however, partially dissolves cellulose-thickened cell walls, freeing up nutrients by breaking down the cell membranes. Several studies report increase in total carotenoids after steam blanching (Howard et al 1999;Sulaeman et al 2001;Puuponen-Pimia et al 2003). Leaching of soluble solids during blanching is the major factor, responsible for apparent increase in carotenoids.…”
Section: Products Developmentmentioning
confidence: 97%
“…Cooking, however, partially dissolves cellulose-thickened cell walls, freeing up nutrients by breaking down the cell membranes. Several studies report increase in total carotenoids after steam blanching (Howard et al 1999;Sulaeman et al 2001;Puuponen-Pimia et al 2003). Leaching of soluble solids during blanching is the major factor, responsible for apparent increase in carotenoids.…”
Section: Products Developmentmentioning
confidence: 97%
“…As reported by Sulaeman et al (2001), the orange colour of carrots and carrot crisps can be described by lightness (L*), redness (a*), yellowness (b*), and Hue parameters. Table 2 shows changes in L*, a* and b* values of carrot crisps for increasing frying times during atmospheric and vacuum frying.…”
Section: Colour Developmentmentioning
confidence: 97%
“…The reduction in the carbohydrate content of fried chips may be due to starch gelatinization at high frying temperature (Bouchon and Aguilera, 2001) and possible migration of free soluble sugars from food to water within the material itself followed by the flow of such water into the frying oil (Guoado et al, 2011). It had earlier been observed that the complexity associated with frying is such that it involved mass transfer which is usually related to oil absorption and water loss together with soluble molecules (Sulaeman et al, 2001;Ikanone and Oyekan, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…The higher oil uptake as observed in fried chips of yellow bitter yam may be attributed to a possible higher oil absorption capacity of the chips. The oil uptake by a food product undergoing frying is usually regarded as a function of volume of oil in the fryer, residence time in the fryer and mass transfer capacity of the product involving oil-water exchange and replacement (Sulaeman et al, 2001, Rojas-Gonzalez et al, 2006. The significance of higher oil content in the fried chips is that it can lead to a rapid induction time for rancidity to occur (Ikoko and Kuri, 2007).…”
Section: Resultsmentioning
confidence: 99%